MURABAHAH, ANTARA TEORI DAN PRAKTEK - Muh. Sholihuddin (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2013)
Islamic bankers assume that an Islamic bank is a bank that is free from riba. Furthermore, conventional banks as the bank alleges that does not comply with the principles of Islamic prisnip. This naturally raises the question, what is like that. Some scientists doubt munslim statement. In fact, there is a presumption of Islamic banks is just trickery to gain profit. Also some say Islamic banking and conventional banking is not just twins, but are conjoined twins. One contract that much attention is murabahah. Akad murabahah is a superior product in Islamic banks as a clear advantage and the risk of loss can be minimized. According to the study, 60-70% of the amount of financing extended by Islamic banks (both Islamic banks and BMT). Of course, this is reasonable since the establishment of Islamic banks, as conventional banks are profit-oriented. However, Islamic banks do not practice it much different from conventional banks, both do not want to lose. Because profit is determined by Islamic banks, where customers can not haggle Profit must be obtained. This ultimately hurt the principle of voluntarism and mutual fairness in the contract. If it is lost, then the contract does is batil and zalim.